HUBUNGAN KEPEMIMPINAN DAN KOMUNIKASI DALAM PENUGASAN TIM DENGAN KELENGKAPAN DOKUMENTASI ASUHAN KEPERAWATAN - Amalia, Amalia (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
The vision, mission and objectives of a hospital from a nursing room greatly influence the establishment of a nursing care assignment method, the availability of nursing staff both in number and qualifications, the level of dependence and mobility of the client and the availability of nursing procedures and standards. The purpose of this study was to identify leadership and communication relationships in team assignments with complete nursing care documentation at the hospital. Using the quantitative method of Cross Sectional design, the research subjects were nurses in the inpatient ward of the Palembang Mother Hospital with a sample of 81 nurses determined using purposive sampling. Data sources were obtained by using questionnaires and interviews, which were conducted on November 24 - December 11 2018. Analysis of data using the chi-square test. The results of leadership research in carrying out team assignment methods were lacking (76.5%) and communication was also lacking (74.1%) while the evaluation of nursing care documentation for completeness was complete (69.1%). For the p-value of the leadership variable (0,836) and communication has p-value (0,749), it is concluded that there is no relationship between leadership and communication in the assignment of the team with complete documentation of nursing care in the inpatient ward of the Bunda Palembang Hospital. Based on the results of the study, it is expected that the management of the hospital will improve its managerial function in improving the quality of nursing services, especially in communication and leadership in evaluating nursing care documentation